Experience on self-assessment and accreditation processes of the Superior Technological Institutes - Escalante, Mónica (2018)
The self-assessment and accreditation processes of the superior technological educational institutes (IEST) conducted by the Council of Assessment, Accreditation and Certification of Quality of Nonuniversity Superior Education (CONEACES) served as a response to a prevailing necessity to promote a culture of quality. The objective was to mobilize change processes that start from an internal assessment, a self-assessment guided to the self-regulation and constant improvement, and that can be directed to an external, impartial and objective fulfillment. The survey had the participatory work as a strategy and the rallying ability as a strength necessary to involve all of the actors related to the IEST: authorities, promoters, directors, teachers, staff members, academicians, national and international experts. Evidence to the study has been more than the 200 IEST that until the end of the year 2014 were in self-assessment process, third party assessment or have already been accredited.